Penerapan Model Pembelajaran Tipe Jigsaw pada Materi “Mekanisme Transport Zat” - Lenny Handayani (Universitas Negeri Makassar, 2022)
Abstract. Learning science is often considered as a learning that is boring and difficult to understand, so we need a learning model that can make science lessons fun and easy to understand. The material